PERHITUNGAN BREAK EVEN POINT (BEP) PADA INDUSTRI RUMAH TANGGA CINCAU BUKIT ERNANI DI BUKIT BESAR – PALEMBANG - Reni Agustina; Jalaluddin Sayuti; Dibyantoro Dibyantoro (LPPM UNIVERSITAS BINA INSAN, 2016)
The purpose of this study was to determine the break-even point based on rupiah and per unit of black grass jelly products, to ensure profit rates and profit plans. In analyzing the problem, the author uses observation, interviews, and uses the Break Even Point (BEP) formula. Based on calculations, Break Even Point from Cincau Ernani Hill in rupiah is Rp. 363,980,247.39 and in units of 97,061 kg and 24,265 trays. In 2016, Cincau Ernani Hill wanted to plan to produce 700,000,000.00. To achieve this profit, it was budgeted that Cincau Ernani Hill must produce black cincau Rp. 1,706,390,833 or 455,037 kg or 113,759 trays.